THE EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. PUTRA BENGAWAN SUKSES BEKASI - Agrasadya Agrasadya; Muger Apriansyah; Ading Sunarto (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to determine the effect of work discipline and work motivation on employee performance either partially or simultaneously. This research was conducted using quantitative research methods involving employees as a sample in this study. Also, this study uses research tests, namely validity test, reliability test, classical assumption test, correlation coefficient test, regression coefficient test, coefficient of determination test, t-test and f test. The results of this study are the variable Effect of Work Discipline (X1), Work Motivation (X2) on Employee Performance (Y) based on data analysis shows that the multiple regression coefficients that have been determined between Work Motivation (X2) and Employee Performance (Y) are Y = Y = 5.570+0.206X1+0.694X2. These results can be concluded that there is a positive relationship between Work Discipline (X1), Work Motivation (X2) on Employee Performance (Y). The constant (a) = 5.570 means that without Work Discipline (X1) and Work Motivation (X2), the Employee Performance value is 5.570 units. The constant (b1) = 0.206 means that if the Work Discipline (X1) of employees increases by one unit, then the value of Employee Performance will increase by 0.206 units. The constant (b2) = 0.694 means that if the employee's work motivation (X2) increases by one unit, the employee's performance value will increase by 0.694 units. The coefficient of determination between work discipline (X1) and work motivation (X2) on employee performance (Y) is R Square (R2) 0.655. It means that Work Discipline (X1) and Work Motivation (X2) on Employee Performance (Y) are 65.5%, and other factors influence the remaining 34.5%. Testing the effect of independent variables together on the dependent variable is carried out using the f test. The results of statistical calculations show the value of Fcount 54.080 > Ftable 3.16. by using a significance limit of 0.05, the significance value obtained is 0.000 < 0.05. The hypothesis states that the simultaneous variable of Work Discipline      (X1), Work Motivation (X2), influences Employee Performance